Respon Pertumbuhan Vegetatif Dan Generatif Bawang Merah Kultivar Lokal Eban Yang Diberi Perlakuan Giberelin (GA3) Dan Pupuk P Di Dataran Menengah Kabupaten Timor Tengah Utara - Anna Tefa; Hermina Manlea; Rikardus Kolo; Antonius Ola; Gebhardus Djugian Gelyaman (Postgraduate, University of Mataram, 2023)
One strategy to increase shallot productivity is to use fertilizers and growth regulators. The aim of the study was to determine the response of vegetative and generative growth of shallots to local Eban cultivars through the application of gibberellins and P fertilizers in the middle plains of North Central Timor District. This study used a factorial randomized block design (RBD). The first factor was the application of gibberellins (GA3), consisting of three treatments, namely without application of GA3 (control), application of 100 ppm GA3 and application of 200 ppm of GA3. The second factor was P fertilizer treatment which consisted of three treatments, namely without P fertilizer (P0), P fertilizer 50 kg/ha (P1) and P fertilizer 100 kg/ha (P2). The results showed that the 200 ppm gibberellin treatment had an effect on plant height. Treatment of 100 ppm gibberellins affected tuber diameter, tuber fresh weight and tuber dry weight. Treatment of P 200 kg/ha had an effect on plant height and number of leaves, treatment of P 100 kg/ha had an effect on the number of tillers. Generative growth did not occur in all the treatments tried, this was due to the influence of environmental factors such as high temperatures during the study